1987
DOI: 10.1177/0093854887014003008
|View full text |Cite
|
Sign up to set email alerts
|

American Death Penalty Attitudes

Abstract: Public support for the death penalty is something of an American tradition. Yet the bases of the American tradition of support for the death penalty are not well understood. An understanding of American attitudes toward capital punishment is important, not only because the United States is again executing criminal offenders, but because it provides a rough estimate of the level of maturity of American civilization. This study critically examines the reasons and processes by which Americans come to support the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…While several researchers observed that death penalty support was positively correlated with fear of crime and/or victimization experience (Bohm, 1987(Bohm, , 1998Ellsworth & Gross, 1994;Rankin, 1979;Smith, 1975;Stinchcombe et al, 1980;Thomas & Foster, 1975), Combs and Comer's (1982) study was the only one that examined the extent to which such influences could account for racial differences in death penalty support. While Combs and Comer (1982) observed significant racial differences in the effects of media exposure and fear of victimization on support for capital punishment, these differences were not substantial enough to attenuate the effect of race on death penalty support, and thereby, account for this troublesome racial divide.…”
Section: Racial Differences In Fear Of Crime and Victimization Experimentioning
confidence: 99%
“…While several researchers observed that death penalty support was positively correlated with fear of crime and/or victimization experience (Bohm, 1987(Bohm, , 1998Ellsworth & Gross, 1994;Rankin, 1979;Smith, 1975;Stinchcombe et al, 1980;Thomas & Foster, 1975), Combs and Comer's (1982) study was the only one that examined the extent to which such influences could account for racial differences in death penalty support. While Combs and Comer (1982) observed significant racial differences in the effects of media exposure and fear of victimization on support for capital punishment, these differences were not substantial enough to attenuate the effect of race on death penalty support, and thereby, account for this troublesome racial divide.…”
Section: Racial Differences In Fear Of Crime and Victimization Experimentioning
confidence: 99%
“…); and another research body that builds either on prejudices (Barkan and Cohn, 1994;Borg, 1997;Gilliam and Iyengar, 2000;Peffley and Hurwitz, 2002), or national traditions (Bohm, 1987(Bohm, , 1991(Bohm, , 1998Lua and Zhang, 2005), thus tapping on a culturalist approach. Much of this literature develops sophisticated statistical analysis and brings interesting results.…”
Section: Introductionmentioning
confidence: 99%
“…The burgeoning literature on death penalty attitudes can be classified in two distinct groups: one that views these attitudes as built on fears and perceptions of discrimination (Cochran and Chamlin, 2006;Halim and Stiles, 2001;Peffley and Hurwitz, 2007), hence claiming a rationalist response to institutional settings where people live (legal framework, justice system, position in the political system, etc. ); and another research body that builds either on prejudices (Barkan and Cohn, 1994;Borg, 1997;Gilliam and Iyengar, 2000;Peffley and Hurwitz, 2002), or national traditions (Bohm, 1987(Bohm, , 1991(Bohm, , 1998Lua and Zhang, 2005), thus tapping on a culturalist approach. Much of this literature develops sophisticated statistical analysis and brings interesting results.…”
Section: Introductionmentioning
confidence: 99%
“…Black Americans believe police officers are more likely to use excessive force compared to White Americans (and to lesser extent Latinx Americans) and generally have more negative views of police overall (Cato Institute, 2016). Researchers have also found a substantial divide in death penalty support between Black citizens and White citizens (Bohm, 1987; Cochran & Chamlin, 2006; Cochran et al, 2003; Young, 1991). Many scholars attribute these perceived differences to racial prejudices in the criminal justice system (Foglia & Connell, 2019; Soss et al, 2003; Unnever et al, 2008).…”
Section: Indirect Supporting Literaturementioning
confidence: 99%